1990
DOI: 10.1002/bit.260350111
|View full text |Cite
|
Sign up to set email alerts
|

In situ methane enrichment in anaerobic digestion

Abstract: A major cost consideration in the use of anaerobic digestion to convert biomass and waste to utility-grade gas is the expense of separating CO(2) from the product gas. Anaerobic digestion has a number of inherent properties that can be exploited to increase the methane content of the gas directly produced by the digester, the most important of which is the high solubility of CO(2)(40-60 times that of methane) in water under digestion conditions. The methane enrichment concept examined in this study involved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 8 publications
6
18
0
1
Order By: Relevance
“…Methane, in contrast, is less soluble and is thereby more dominant in the gas phase. This phenomenon was observed by the authors [4] and also reported in several other studies [12][13][14].…”
Section: Introductionsupporting
confidence: 84%
“…Methane, in contrast, is less soluble and is thereby more dominant in the gas phase. This phenomenon was observed by the authors [4] and also reported in several other studies [12][13][14].…”
Section: Introductionsupporting
confidence: 84%
“…At a higher pressure, more CO 2 is dissolved in the liquid and then CH 4 becomes dominant in the gas phase. Methane enrichment in anaerobic digestion under pressure was also documented elsewhere [5][6][7]19]. However, in terms of the absolute value, the methane content was not as high as reported in other studies.…”
Section: Biogas Compositionsupporting
confidence: 54%
“…The reported few trials showed that pressurized anaerobic digestion had the potential to produce biogas of natural gas quality [6,7]. However, all the experiments were carried out under low organic loading rate (OLR) and a fixed pH value.…”
Section: Introductionmentioning
confidence: 99%
“…natural gas, used in vehicles and other machinery. Compared with in situ gas purifications which take advantages of differing solubility of CH 4 and CO 2 by controlling pH or pressure [13,14], the new process has no negative effect and increase CH 4 production significantly.…”
Section: Performance Of Mec-ad Coupling Systemmentioning
confidence: 99%